Pregnancy Outcome in Gestational Diabetes Mellitus under Treatment-Bangladesh Perspective - Yasmin-Aktar; A Hasanat M; Sharmin-Jahan; Nusrat-Sultana; Mashfiqul-Hasan; Sandesh-Panthi; Atiqur-Rahman M; Fariduddin M (Journal of Bioinformatics And Diabetes, 2017)
Objectives: To observe pregnancy outcomes in gestational diabetes mellitus (GDM) under treatment. Methods: Pregnant mothers (N=191) diagnosed with GDM (n=91, age: 27.44±4.91yr; body mass index, BMI: 26.88±4.16 kg/m2; mean±SD) on the basis of WHO 2013 criteria were compared with non-GDM (n=100, age: 26.01±4.81yr, BMI: 25.53±3.77 kg/m2, mean±SD) for pregnancy outcome irrespective of gestational age. HbA1c was also measured in all mothers. Gestational hypertension, preeclampsia, premature rupture of membrane (PROM), hydramnios, recurrent urinary tract infection (UTI), recurrent moniliasis, intrauterine growth retardation (IUGR), intra uterine death (IUD), mode of delivery, birth weight, birth injury, neonatal hypoglycemia, hyperbilirubinemia, respiratory distress syndrome (RDS), congenital anomaly were recorded at every trimester. 160 mothers (GDM=75, non-GDM=85) could be followed for outcomes to the end of pregnancy. All the GDM mothers were offered standard treatment throughout pregnancy period. Results: HbA1c was significantly higher in GDM than that in non-GDM (5.42±0.61 vs. 4.98±0.44%, mean±SD; p<0.001).Outcome events in GDM and non-GDM were: gestational hypertension- 3.6% vs. 2.3% (p=0.621), preeclampsia- 2.4% vs. 0% (p=0.150), PROM- 4.9% vs. 0% (p=0.037), hydramnios- none in any group, recurrent UTI- 12.3% vs. 4.7% (p=0.073), recurrent moniliasis- 0.0% vs. 2.3% (p=0.165), caesarian section- 85.3% vs. 72.9% (p=0.056), small for gestational age (SGA)- 26.4% vs. 36.7% (p=0.246), large for gestational age (LGA)- 1.4% vs. 0%, p=0.246, IUGR- 2.3 vs. 2.5% (p=0.952), neonatal hypoglycemia- 2.7% vs. 0.0% (p=0.130), hyperbilirubinemia- 12.0% vs. 11.8% (p=0.963), RDS- 0.0% vs. 2.4% (p=0.181) and birth injury- 0.0% vs. 1.2% (p=0.346), congenital anomaly- 4.0% vs. 1.2% (p=0.254) and abortion- 1.3% vs. 0.0% (p=0.286). Preterm delivery (12.0% vs. 7.1%, p=0.285) and caesarean section (85.3% vs. 72.9%, p=0.056) were more in GDM. Conclusions: Despite treatment, adverse events were relatively higher but non-significant in GDM.
Keywords: GDM